The Association among Physical Activity, Sociodemographic, Trunk Muscles Thickness and Low Back Pain-Related Disability in Amateur Soccer Players: An Observational Study - Miñambres-Martín, Diego; Antonio Valera-Calero, Juan; Martín-Casas, Patricia; Varol, Umut; Fernandez-de-las-Penas, Cesar; Plaza-Manzano, Gustavo (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2023)
Objective Although low back pain (LBP) is one of the most common musculoskeletal disorders, there is limited evidence assessing which factors contribute LBP severity in amateur athletes. We aimed to analyze relationships between sociodemographic, clinical, lifestyle and lumbar multifidus (LM) at L4 and L5 levels, rectus abdominis (RA), external and internal obliques (EO and IO) and transversus abdominis (TrA) muscles thickness assessed with ultrasound imaging (US) variables with lumbar disability in amateur athletes with LBP and lumbar disc herniation.Methods Eighty-two male amateur soccer athletes were analyzed. Demographic data, internal hip rotation, finger-floor distance, pain intensity, number of LBP episodes within the last year, metabolic equivalent of tasks for physical activity, sitting time, muscle thickness and disability caused by LBP were collected.Results Pain intensity showed significant associations with LBP recurrence, disability, sedentarism, trunk and hip flexibility, vigorous physical activity and TrA, EO and RA muscles thickness (p<0.05). Similarly, disability was associated with number of LBP episodes, vigorous activity, sitting time, finger floor distance, and RA, EO and IO muscles thickness (p<0.05). TrA thickness and internal hip rotation were not associated with lumbar disability (p>0.05).Conclusion LBP intensity and pain-related disability were significantly associated with LBP episodes, vigorous activity, sitting time, finger floor distance, and thickness of abdominal muscles were associated with pain intensity and disability. However, lumbar multifidus thickness at rest, ankle dorsiflexion and walking time were not associated with clinical severity.
Keywords: low back pain; rehabilitation targets; quality-of-life